The SCUBA-2 Cosmology Legacy Survey: multi-wavelength properties of ALMA-identified submillimeter galaxies in UKIDSS UDS - Simpson, J.M.; Smail, Ian; Swinbank, A.M.; Ivison, R.J.; Dunlop, J.S.; Geach, J.E.; Almaini, Omar; Arumugam, Vinodiran; Bremer, M.N.; Chen, Chian-Chou; Conselice, Christopher J.; Coppin, K.E.K.; et al. (American Astronomical Society, 2017)
We present a multi-wavelength analysis of 52 submillimeter galaxies (SMGs), identified using ALMA 870 μm continuum imaging in a pilot program to precisely locate bright SCUBA-2-selected submillimeter sources in the UKIDSS Ultra Deep Survey (UDS) field. Using the available deep (especially near-infrared) panoramic imaging of the UDS field at optical-to-radio wavelengths we characterize key properties of the SMG population. The median photometric redshift of the bright ALMA/SCUBA-2 UDS (AS2UDS) SMGs that are detected in a sufficient number of wavebands to derive a robust photometric redshift is z = 2.65 ± 0.13. However, similar to previous studies, 27% of the SMGs are too faint at optical-to-near-infrared wavelengths to derive a reliable photometric redshift. Assuming that these SMGs lie at z gsim 3 raises the median redshift of the full sample to z = 2.9 ± 0.2. A subset of 23 unlensed, bright AS2UDS SMGs have sizes measured from resolved imaging of their rest-frame far-infrared emission. We show that the extent and luminosity of the far-infrared emission are consistent with the dust emission arising from regions that are, on average, optically thick at a wavelength of ${λ }_{0}\geqslant 75\,μ {\rm{m}}$ (1σ dispersion of 55–90 μm). Using the dust masses derived from our optically thick spectral energy distribution models, we determine that these galaxies have a median hydrogen column density of N H = 9.8${}_{-0.7}^{+1.4}$ × 1023 cm−2, or a corresponding median V-band obscuration of A v = 540${}_{-40}^{+80}$ mag, averaged along the line of sight to the source of their rest-frame ~200 μm emission. We discuss the implications of this extreme attenuation by dust for the multi-wavelength study of dusty starbursts and reddening-sensitive tracers of star formation.